G176(P) A case of kocher-debre-semelaigne syndrome (KDSS) associated with renal dysfunction. (24th May 2017) - Fordham, J; Kumar, Y; Aamir, T
Abstract : Aim: To report an unusual case of KDSS with the rare combination of renal dysfunction. Methods: Description of the case with review of the literature. Results: A 14 year old boy was referred with elevated creatinine found on investigation for leg cramping. Further history included reduced activity, poor appetite, daytime sleepiness and constipation for 2 years duration. On examination were typical facial and body habitus of a child with longstanding severe hypothyroidism. There was also marked hypertrophy of the calf muscles. Blood tests revealed elevated TSH (>100 mIU/L), repressed T3 and T4 (0.3 mcg/dL), elevated creatine kinase (5378 IU/L) and elevated thyroid peroxidase antibodies (41.7 IU/mL). Renal ultrasound scan showed a slightly small right kidney but cortical preservation bilaterally. Muscle ultrasound and follow-up blood tests are pending. Treatment with thyroxine was commenced based on a diagnosis of KDSS. This is an association of hypothyroidism and muscular pseudohypertrophy seen in childhood. The underlying thyroid defect can vary from acquired (autoimmune, as in this case) to congenital. As such the syndrome, though rare worldwide, is significantly more so in countries that screen for congenital hypothyroidism 1 . At presentation, features of hypothyroidism are usually florrid and complications such as acute compartment syndrome and rhabdomyolysis may occur 1 . Muscle biopsy is rarely necessary and if performed, histology tends to be non-specific. Muscle cramping is a known association with the muscular pseudohypertrophy in this syndrome. These abnormalities, as well as the clinical features of hypothyroidism, revert with treatment of the hypothyroidism, though final height may still be reduced 2 . To our knowledge renal dysfunction as an isolated association with this syndrome has never been reported. Conclusion: This case highlights a rare cause of myopathy that is important not least because of its often complete reversibility with treatment of the underlying hypothyroidism. It also introduces an association with renal dysfunction.